Paper towns [videorecording (DVD)] - Wolff, Nat, 1994-; Delevingne, Cara, 1992-; Abrams, Austin; Green, John, 1977- (Twentieth Century Fox Home Entertainment, 2015)
Adapted from the bestselling novel by author John Green, a coming-of-age story centering on Quentin and his enigmatic neighbor Margo, who loved mysteries so much she became one. After taking him on an all-night adventure through their hometown, Margo suddenly disappears; leaving behind cryptic clues for Quentin to decipher. The search leads Quentin and his quick-witted friends on an exhilarating adventure that is equal parts hilarious and moving.